Selective Extraction of Ni from Superalloy Scraps by Molten Mg-Zn - Qinghua Tian; Xiangdong Gan; Fuhui Cui; Dawei Yu; Xueyi Guo (Metals, 2021)
Bearing significant concentrations of high value and critical metals, superalloy scraps require comprehensive recycling for metal reclamation. In this study, nickel-based superalloy was treated with molten Mg-Zn for the selective extraction of nickel. The influence of heating temperature, the molar ratio of Mg to Zn in the molten metal, Mg-Zn/superalloy mass ratio, and heating time on metal extraction were investigated. Using the heating temperature of 800 °C, the Mg/Zn molar ratio of 9/1, the Mg-Zn/superalloy mass ratio of 5/1, and heating time of 240 min, the extraction rate of 97.1% was achieved for Ni, and the extraction rates of Fe, Cr and refractory metals (Nb, Mo and Ti) were all less than 1%. In the subsequent vacuum distillation process, nickel with a purity of 98.3 wt% was obtained. Therefore, the proposed method is a short, clean, and efficient process for selectively extracting nickel from the superalloy scraps.